2019
DOI: 10.29309/tpmj/2019.26.04.3363
|View full text |Cite
|
Sign up to set email alerts
|

Mandibular Fracture Management;

Abstract: ABSTRACT… Objectives: To compare the efficacy of Maxillomandibular fixation screws versus Erich Arch bar in the management of mandibular fractures. Study Design: Comparative case series study. Setting: . Period: 29/03/2016 to 28/09/2016. Methodology: Forty patients of either gender with age above 18 years with mandibular fracture requiring closed reduction were included. 20 patients of Groups A, treated with Maxillomandibular fixation screws and 20 patients of Group B treated with Erich Arch bar. Mean operativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Amongst the face, mandible becomes the most susceptible site. (11) The results of this study revealed that the mean age was 27.24 + 13.564. The majority of patients were males i.e.…”
Section: Figure 3: Yearly Distribution Of Etiology Of Mandibular Fracmentioning
confidence: 65%
“…Amongst the face, mandible becomes the most susceptible site. (11) The results of this study revealed that the mean age was 27.24 + 13.564. The majority of patients were males i.e.…”
Section: Figure 3: Yearly Distribution Of Etiology Of Mandibular Fracmentioning
confidence: 65%
“…The arch bar's length is also adjustable to the work area, and its installation is relatively simple. 20 Placing eyelets is a wire splinting technique that requires 0.4 mm-diameter wire placed on the left and right maxillary posterior teeth. The placement of eyelets on the maxilla serves as an instrument for MMF.…”
Section: Discusionmentioning
confidence: 99%